Peningkatan Produktivitas UKM Lontong Plastik Mini Modern di Desa Kolam - Vega Liana; Rima Rizki Syahputri; Putri Ayuni; Gita Kurnia Sari Sembiring; Zainarti Zainarti (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
SMEs are small and medium enterprises owned by individuals or individual business entities. Small and Medium Enterprises (SMEs) have an important role in supporting the national economy. Therefore, SMEs need to get attention from the government and academics. Various processed food products are produced by SMEs. Lontong is one of the staple food products that we often encounter and consume. Lontong is made from rice wrapped in plastic, banana leaves and boiled. The majority of Lontong business owners continue to produce their goods using firewood and improvised tools. As a result, the quality and production capacity remain low. However, on this occasion the researchers conducted research on the mini Lontong UKM located in the village of Pond, Kab. Deli Serdang Kec. Percut Sei Tuan here, researchers see the production process for making rice cake at Mrs. Risna's house. The manufacturing process is very modern because it uses modern cooking utensils, namely using a gas stove and the cooking process takes 6 hours faster. The mini size of the lontong and the cheap and economical price makes it attractive for the public to buy the product and the owner distributes it to markets and online media such as social media and other online media. Keywords : Lontong UKM, Productivity, Production Marketing